2014
DOI: 10.1007/s00540-014-1792-z
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between rosuvastatin and rocuronium in rat sciatic-gastrocnemius nerve-muscle preparation

Abstract: The neuromuscular blocking potency of rocuronium is increased and recovery is delayed in rats that pre-treated with rosuvastatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Considering the pharmacokinetics, disposition, and liver-specific distribution of rosuvastatin in vivo, we calculated the concentration, which ranged from 1 to 100 mmol/L. Additionally, the dosages of rosuvastatin previously used in the rat model were 2 mg/kg/day, 25 5 mg/kg/ day, 19 10 mg/kg/day, and 15 mg/kg/day. 20 The dosage we used in vivo was within the range of previously reported studies.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the pharmacokinetics, disposition, and liver-specific distribution of rosuvastatin in vivo, we calculated the concentration, which ranged from 1 to 100 mmol/L. Additionally, the dosages of rosuvastatin previously used in the rat model were 2 mg/kg/day, 25 5 mg/kg/ day, 19 10 mg/kg/day, and 15 mg/kg/day. 20 The dosage we used in vivo was within the range of previously reported studies.…”
Section: Discussionmentioning
confidence: 99%
“… showed that depolarizing NMBA succinylcholine caused minor muscle injuries in patients taking statins for over 3 months. One study showed that pre‐treatment with rosuvastatin delayed the recovery and increased the blocking potency of the non‐depolarizing NMBA rocuronium in sciatic gastrocnemius nerve muscle preparation of rat . The effect of statins on non‐depolarizing NMBA is unclear in a clinical setting.…”
mentioning
confidence: 99%